The Literary History of the Igbo Novel African Literature in African Languages - Emenyonu, Ernest N. (2020)
This book looks at the trends in the development of the Igbo novel from its antecedents in oral performance, through the emergence of the first published novel, Omenuko, in 1933 by Pita Nwana, to the contemporary Igbo novel. Defining "Igbo literature" as literature in Igbo language, and "Igbo novel" as a novel written in Igbo language, the author argues that oral and written literature in African indigenous languages hold an important foundational position in the history of African literature. Focusing on the contributions of Igbo writers to the development of African literature in African languages, the book examines the evolution, themes, and distinctive features of the Igbo novel, the historical circumstances of the rise of the African novel in the pre-colonial, era and their impact on the contemporary Igbo novel. This book will be of interest to scholars of African literature, literary history, and Igbo studies.